Use of low-level grain supplementation in an intensive-early stocking program: influence on daily gain and forage production - Cochran, R.C.; Vanzant, E.S.; Brandt, Robert T., Jr.; Owensby, Clenton E.; Auen, Lisa M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 4-year experiment was conducted to evaluate the effect of increasing amounts of grain supplementation on steer gains and forage production in pastures managed under an intensive-early stocking system. Average daily gain tended to increase in direct proportion to increasing level of sorghum grain supplementation (2.19, 2.43 and 2.59 lb/day for the control, 2 and 4 lb/day supplement levels, respectively). The amount of grass remaining in the pastures at the end of the grazing season (approximately July 15) also increased in direct proportion to increasing sorghum grain supplementation. Forage remaining in the pastures at the end of the growing season (approximately October 1) tended to respond in a similar manner.
Keywords: Beef; Intensive-early stocking; Supplementation; Sorghum grain; Milo